Mohr e Kharman : Symbol, Based on an Unwritten Customary Treaty in Villages - Morteza Salemi Ghamsari; Hossein Sadeghi (Dānishhā-yi būmī-i Īrān, 2016)
By the time of the 1300s, the stamp was used instead of today's signature. Everyone had his own personal seal and each stamped paper was legally considered as an official document. One of the most common stamps in the villages was the Mohr e Kharman. It was a common practice to use the stamp of a trench, a harvest, to keep others from reaching wheatgrass in the village. In this way, when harvesting and preparing wheat, the representative of the owner or the owner was present at each fields in the village, and sealed the harvest with a wooden stamp, so that nobody would snap at night. The stamp of a trench is an example of a locksmith whose guarantee of solidity is not an object or part of its own; the kind is not material and no technology has been used to make it. In his guarantee of solidarity, Mohr kharman enjoyed the strength of the land system. Here, an unwritten and unofficial rule, found a custom and tradition narrative and concentrated in the existence of an object. It was so that the seals, were guardians without ears and eyes, and in addition to the backing of the ruling system, they also had the backing of the community's faith. The sacred and blessed roles and words on all kinds of seals and on the harvest seals have had such a function. This article applies ethnographic method and interviews with two local and academic informants and has used books that have, though little, addressed this subject.